RELATIONSHIP BETWEEN GUILD CONFORMITY AND LOYALTY OF MASSIVELY MULTIPLAYER ONLINE ROLE-PLAYING GAME (MMORPG) GAMERS - Ediwan Farid Fahmadi; Prasetyo Budi Widodo; Nofiar Aldriandy Putra (Faculty of Psychology, Diponegoro University, 2013)
This study aimed to determine the relationship between guild conformity and loyalty of MMORPG (Massively Multiplayer Online Role-Playing Games) gamers in Semarang.Subjects in this study were selected purposively, ie 15-30 year-old gamers, play MMORPG, join in a guild, located in Semarang, and willing to participate in this study. Data collected in this study using a Likert scale form compiled by researchers, namely gamer loyalty scale consists of 21 items (reliability coefficient = 0.918) and the guild conformity scale consisting of 16 items (reliability coefficient = 0.863).Analysis of data using the correlation test of Karl Pearson Product Moment to determine the relationship between guild conformity and loyalty of MMORPG gamers. The results showed a significance value of 0.908 (p> 0.005), which suggests that the relationship between the two variables is not significant. Therefore, there was no significant relationship between guild conformity and loyalty of MMORPG gamers.